When Dengue and Lupus Collide: A Case Report of Overlapping Symptoms Leading to Diagnostic Delay - Kadek Nova Adi Putra; I Ketut Suryana (Archives of The Medicine and Case Reports, 2025)
Systemic lupus erythematosus (SLE) and dengue fever are two distinct diseases with overlapping clinical presentations, posing diagnostic challenges, especially in tropical regions where dengue is endemic. This case report describes a patient initially diagnosed with dengue fever who was later found to have SLE, highlighting the importance of considering SLE in the differential diagnosis of fever and thrombocytopenia even during dengue outbreaks. A 52-year-old female presented with fever, thrombocytopenia, arthralgia, myalgia, and a rash. She was initially diagnosed with dengue fever based on her clinical presentation and the prevalence of dengue in her community. However, her condition did not improve with supportive treatment, and she developed new symptoms, including shortness of breath and pleural effusion. Further investigations revealed a positive antinuclear antibody (ANA) test, leading to a revised diagnosis of SLE. The patient responded well to corticosteroid therapy and was discharged after seven days. In conclusion, this case underscores the importance of maintaining a broad differential diagnosis when evaluating patients with fever and thrombocytopenia in dengue-endemic areas. A high index of suspicion for SLE is crucial, even during dengue outbreaks, to ensure timely diagnosis and appropriate management.